Mechanical and Thermal Properties of Bamboo Textile Waste Reinforced Recycled Polypropylene Composites for Sustainable Packaging Applications - Nur Ain Mohd Amin; Mazatusziha Ahmad; Reazul Haq Abdul Haq (Progress in Engineering Application and Technology, 2026)
The ever-increasing amount of textile and plastic waste has become a serious issue for the environment, especially in Malaysia, which has disposed off massive amounts of textile and plastic packaging waste to landfills every year. Recycling these types of waste into value-added materials has become the need to promote sustainable development and the concept of a circular economy. Despite the rise in demands for sustainable composites, bamboo textile waste as a reinforcing material and recycling polypropylene with poor interfacial bonding properties between natural fibers has been uncommon. This paper proposes to analyze the influence of alkaline treatment and bamboo textile waste ratio on the mechanical and thermal properties of recycling polypropylene composites for sustainable packaging. Bamboo textile waste was treated with 5% NaOH solution and was added to recycling polypropylene with fiber loading of 5 to 25 wt%, using MAPP as the coupling agent. Fiber analysis was done using FESEM and FTIR analysis, whereas the tensile test was performed using the universal testing machine. Analysis for the thermal property was done using the TGA scan and the DSC analysis. Results showed that the treatment removed significant hemicellulose and lignin content, which proved to be effective for increasing the roughness of the fibers and the bonding properties between the fibers and the polypropylene. TGA and DSC analysis revealed improvements in the thermal properties of the composites with the presence of the treated fibers. If the present work uses alkaline treatment on the textile fibers to enhance the bonding properties between the fibers and recycling polypropylene, then there will be immense potential for recycling polypropylene to be used as sustainable composites.